SHALLOW-TAPERED CHIRPED FIBER BRAGG GRATING SENSORS FOR DUAL REFRACTIVE INDEX AND TEMPERATURE SENSING - Ayupova, Takhmina; Shaimerdenova, Madina; Tosi, Daniele (MDPI AG, 2021)
In this work, we present a gold-coated shallow-tapered chirped fiber Bragg grating (stCFBG) for dual refractive index (RI) and temperature sensing. The stCFBG has been fabricated on a 15-mm long chirped FBG, by tapering a 7.29-mm region with a waist of 39 µm. The spectral analysis shows two distinct regions: a pre-taper region, in which the stCFBG is RI-independent and can be used to detect thermal changes, and a post-taper region, in which the reflectivity increases significantly when the RI increments. We estimate the RI and thermal sensitivities as 382.83 dB/RIU and 9.893 pm/◦C, respectively. The cross-talk values are low (−1.54 × 10−3 dB/◦C and 568.1 pm/RIU), which allows an almost ideal separation between RI and thermal characteristics. The stCFBG is a compact probe, suitable for long-term and temperature-compensated biosensing and detection of chemical analytes.
Keywords: Chirped fiber Bragg grating; Type of access: Open Access; Dual sensing; Fiber Bragg gratings; Fiber tapers; Optical fiber sensors; Refractive index sensor